Brain Rot and Students Motivation: A Study of Impacts, Contributing Factors, and Digital Literacy-Based Solution Design - Marissa S. Tupamahu; Sherly Gaspersz; Claudia Debora Boekorsyom (Jurnal Pendidikan Bahasa Inggris Undiksha, 2026)
This study examines the relationship between brain rot and students’ learning motivation by analyzing its impacts, contributing factors, and digital literacy-based solutions. A mixed-methods approach was employed, involving 120 senior high school students from four public and private schools in Sorong, Southwest Papua. Quantitative data were collected through a structured questionnaire measuring brain rot exposure and learning motivation using Likert-scale items. Descriptive statistics and Pearson’s Product-Moment Correlation were applied to examine the strength and direction of the relationship between variables after testing normality assumptions using the Kolmogorov-Smirnov test. Qualitative data were gathered through focus group discussions and semi-structured interviews. Thematic analysis following Braun and Clarke’s six-phase framework was used to identify recurring patterns, supported by triangulation and member checking to ensure trustworthiness. The Pearson correlation analysis revealed a very weak and non-significant relationship between brain rot and learning motivation (r = 0.051; p = 0.583), indicating that brain rot is not a strong linear predictor of students’ motivation. In contrast, the qualitative findings revealed a more nuanced picture. Excessive use of social media, particularly Instagram and TikTok, contributed to symptoms of brain rot, such as fatigue, lack of concentration, academic procrastination, and decreased intrinsic motivation. On the other hand, students also reported positive experiences, including exposure to motivational content, the use of videos and animations as alternative learning media, and the integration of academic tasks into social media, which enhanced engagement and motivation. These findings highlight the paradoxical role of brain rot: while it may hinder focus and persistence, it also holds potential as a creative and engaging learning resource when used effectively. The study concludes that the relationship between brain rot and learning motivation is contextual rather than linear, shaped by students’ self-regulation and digital literacy. Accordingly, educators are encouraged to design structured digital literacy programs that redirect social media use from passive consumption toward productive practices that foster academic achievement.